Study Of The Assortment Of Antioxidant And Hemostatic Medicines Registered In The Republic Of Uzbekistan (Journal of Pharmaceutical Negative Results, 2023)
An analysis of the range of antioxidant and hemostatic preparations registered in the Republic of Uzbekistan was carried out on the basis of information from the State Registers of Medicines, Medical Devices and Medical Equipment: 2019 No. 23, 2020 No. 24, 2021 No. 25.The sales volume of hemostatic drugs in the Uzbek market in 2019-2021 was studied based on DRUG AUDIT data.